Assessment of latent tuberculosis infection pre-immunomodulatory therapy; 5 year experience in a UK centre. (January 2022) - Laundy, Nicholas; Colley, Shaun; Fawcett, Joanna; Ryder, Lucy; Vedio, Alicia; Cohen, Danielle; Collini, Paul
Highlights: A 5 year retrospective review of 367 LTBI referrals to a UK TB service. 51% were referred pre-immunomodulatory therapy with 25 different agents. They were older and had more negative & indeterminate screening IGRAs than 'traditional' LTBI referrals. 57% either didn't initiate or couldn't complete chemoprophylaxis. Abstract: Background: An ever greater variety of immunomodulatory agents with potential to reactivate latent TB infection are being used in clinical practice. We set out to describe the experience of assessing and mitigating TB reactivation risk for patients planning to start immunomodulatory biological or small molecule inhibitor (SMI) therapies referred to a TB service in a high income low TB prevalence setting. Methods: Retrospective clinical case note review of patients referred to the infectious diseases TB service of Sheffield Teaching Hospitals following LTBI screening between 1 September 2015 and 30 September 2020. Results: 367 patients had been referred and assessed. 179 patients referred for new entrant or contact screening and 188 (51%) patients were being worked up pre-immunomodulatory therapy with 25 different biologic/SMIs for more than 20 conditions. This group were older (median age 56.2 vs 32.6 years, p < 0.0001), and more likely to have had a negative or indeterminate screening IGRA (25.5% vs 4.1%, p < 0.0001). 155/188 were diagnosed with LTBI, of whom 58% commenced chemoprophylaxis (50 isoniazid, 40 rifampicin/isoniazid) and they were significantly younger than those who did not (median age 48.7 vs 70.6 years, p = 0.0004). 75% completed chemoprophylaxis with 7% stopping early due to altered liver function tests and 10% due to other adverse effects. No differences were observed between isoniazid or rifampicin/isoniazid treated groups. Conclusions: Increased age, less reliable screening IGRAs and adverse effects of chemoprophylaxis in the face of a widening variety of agents make management of LTBI in patients pre-immunomodulatory therapy complex. Better tests and treatments are required.